Optimization of Porang Plant Drying Using Sensors Based on Arduino Microcontroller - Roza, Yuni; KH, Musliadi; Ismail, Asriyani; Pernando, Yonky (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2025)
Drying remains one of the most critical post-harvest challenges in porang tuber processing. Traditional methods, which depend on sunlight and require large areas, are time-consuming and often inconsistent, leading to unstable production and reduced efficiency. This study proposes an Arduino microcontroller-based drying system equipped with a DHT11 sensor to optimize the process. The development followed the ADDIE framework analysis, design, development, implementation, and evaluation to ensure systematic outcomes. Experimental results show that the system effectively maintains controlled conditions. The DHT11 sensor accurately detected temperature in the range of 35–40°C and above, with real-time monitoring displayed on an LCD. Trials demonstrated that heating for less than four hours produced tubers that remained moist, while durations of four to eight hours yielded consistently dry tubers. These findings confirm the reliability of the system in accelerating drying while preserving product quality. Beyond technical efficiency, the system reduces dependency on unpredictable weather, minimizes post-harvest losses, and improves farmer productivity. Its affordability and scalability make it applicable for small to medium agribusinesses, while its adaptability opens opportunities for use with other commodities. Thus, this research contributes not only to technological innovation but also to sustainable agricultural practices and rural economic empowerment.